Melatonin promotes osteoblastic differentiation and regulates PDGF/AKT signaling pathway. (2nd October 2019) - Zhu, Guiling; Ma, Bin; Dong, Penghong; Shang, Junjun; Gu, Xiaochuan; Zi, Ying
Abstract: Melatonin has been reported to participate in bone metabolism in recent studies. However, the underlying mechanism in melatonin‐mediated osteoblastic differentiation remains largely unknown. The aim of this study is to investigate the role of melatonin in osteoblastic differentiation. In the present study, additional melatonin significantly promoted osteoblastic differentiation of MC3T3‐E1 cells as evidenced by increased messenger RNA (mRNA) levels of osteogenic markers, alkaline phosphatase (ALP), collagen type I α1 chain, osteocalcin, and runt‐related transcription factor 2 (Runx2). It was noteworthy that the expression level of platelet‐derived growth factor subunit B (PDGFB) and content of its homodimer PDGF‐BB were remarkably increased after melatonin administration. Moreover, the mRNA levels of phosphorylated PDGFRβ (PDGF receptor β) and Akt, a serine/threonine‐specific protein kinase, were significantly upregulated in melatonin‐treated MC3T3‐E1 cells determined by a real‐time polymerase chain reaction. Besides, by performing alizarin red staining, osteoblastic differentiation of MC3T3‐E1 cells was conspicuously promoted by melatonin, which could be partially attenuated by crenolanib, a PDGFR inhibitor. Similarly, results from immunofluorescence and western blot assay showed that melatonin‐induced upregulation of Runx2 and phosphorylated Akt was suppressed by crenolanib. Akt inhibition by MK‐2206 also suppressed osteoblastic differentiation. Furthermore, by in vivo assay, additional melatonin promoted osteoblastic differentiation in mice with femoral fracture, and obvious callus formation was observed in melatonin‐treated mice 5 weeks after fracture. Melatonin supplement also inhibited osteoclastic differentiation in mice. All statistical analysis was performed using GraphPad Prism and a P  < 0.05 was deemed to be significant. To summarize, we demonstrate that melatonin promotes osteoblastic differentiation in MC3T3‐E1 cells and enhances fracture healing in mouse femoral fracture model and regulates PDGF/AKT signaling pathway.